Quantificação do metabolismo aeróbio e anaeróbio de levedura alcoólica por método estequiométrico - Venturini Filho, Waldemar Gastoni [UNESP] (2014)
The aim of this study was to quantify aerobic (respiration) and anaerobic (alcoholic fermentation) metabolisms using a stoichiometric approach for several yeasts (Apti, Fleischmann, Mauri, Pakmaya and Uniferm) during sugarcane must fermentation and during Fleischmann’s fermatation of grape, malt, and sugarcane musts. Treatments were conducted in triplicates. From carbon dioxide and ethanol mass produced, it is possible to determine, by stoichiometric calculations, the percentage of sugar respired and fermented. Fleischmann showed higher respiration rate in sugarcane must (14,21%) than in grape (10,85%) and malt (11,17%) musts. Yeasts produced in Brazil (Fleischmann and Mauri) presented respiratory rates greater than 10% while the others (Apti, Pakmaya and Uniferm) showed rates below 10%. The stoichiometric method herein used to estimate aerobic and anaerobic metabolisms during musts fermentation proved to be a practical and yet simple tool that could be used in teaching, research and industrial activities.